Pengaruh Rimpang Kunyit (Curcuma domestica, Val.) terhadap Bakteri Usus secara in vitro - Soegiantoro, Didiek Hardiyanto; Soegiantoro, Gregory Hope; Waruwu, Intan Selvyanti; Theressia, Yanti Octavia (FARMASIS: Jurnal Sains Farmasi, 2021)
The use of turmeric rhizome to treat diarrhea is written in the original Indonesian medicinal manuscript. Diarrhea disease is still a public health problem in Indonesia, because of its high morbidity and mortality. The morbidity survey conducted by Indonesian Ministry of Health shows an increasing incidence trend. One of the causes of diarrhea is an uncontrolled increase in the number of intestinal bacteria and infection by intestinal pathogenic bacteria. This study aims to determine the effect of the turmeric rhizome preparation process, both traditionally and by extraction method by maceration and soxhletation on antibacterial activity, especially intestinal bacteria, so that it can be applied by the traditional medicine industry as well as traditional herbal medicine sellers (“jamu gendong”). The research method used was to test the antibacterial activity of fresh turmeric juice, pre-dried turmeric juice, turmeric extract by maceration using 95 percent ethanol, and turmeric extract by soxhletation at 100 degrees celcius using 95 percent ethanol. The intestinal bacteria used in this study were Escherichia coli, Yersinia enterolitica, Vibrio nonagglutinable, and Shigella flexneri. The results of this study indicate that the treatment process using the traditional method, both fresh turmeric juice and pre-dried turmeric juice, does not show any antibacterial activity. Turmeric extract by maceration showed antibacterial activity against all bacterias and the greatest against Vibrio nonagglutinable bacteria. Turmeric extract by soxhletation showed antibacterial activity against all bacterias and the greatest against Vibrio nonagglutinable bacteria. The conclusion of this study is that the most appropriate method used to process turmeric rhizome as a medicine for diarrhea caused by bacteria is the extraction method by maceration or soxhletation. The greatest antibacterial effect is against the Vibrio nonagglutinable bacteria.